Evaluation of failure behaviour of sheet metals - Affronti, Emanuela (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
The full exploitation of sheet metal formability is crucial for process optimization. This applies in particular to the automotive industry, in which the current trend is in the development of lightweight structures. Nevertheless, the standard evaluation methodology shows weaknesses for brittle materials. In the present study, a detailed analysis of the failure mechanisms for different material classes was carried out to improve the failure limit evaluation. The aim was to analyse the validity of the definition of the onset of necking in order to assure the correct prediction of the deformation limits, including those that do not show any localizations. The knowledge gained was used to define a validity window using pattern recognition methodology and to optimize the forming limit evaluation while taking into consideration the peculiarities of the different material